Imaging of external auditory canal fractures associated with maxillofacial traumas by CBCT - Sinem Coşkun; Hatice Boyacıoğlu; Sema Dural (Selcuk Dental Journal)
Background: The external auditory canal (EAC) is a frequently disregarded region in the assessment of maxillofacial traumas (MFT). The anterior and inferior walls of EAC occur from the tympanic portion of the temporal bone. Tympanic plate is in close proximity with temporomandibular joint. Posterior and anteromedial dislocation of the condyle can result with fracture in the tympanic plate when the condyle is forced against to EAC. The aim of this study to evaluate association with MFT and EAC fractures by using Cone Beam Computed Tomography (CBCT).Methods: CBCT images of 65 patients undertaken between 2016 and 2019 were assessed by one observer to detect the probable EAC, maxilla, mandible and condyle fractures. Descriptive and detailed statistics were performed using SPSS version 20.0 (IBM, USA). Intra-observer reliability was calculated using Weighted Cohen's kappa coefficients.Results: EAC fracture was determined in 40 % of the patients. Of the EAC fractures, 47.4 % and 41.7 % were associated with maxillary and mandibular fractures, respectively. Of the EAC fractures, 42.3 % were bilateral. Left and right condyle fractures were detected together with 41.7 % and 45.5 % of the related side EAC fractures, respectively. Chi‐squared test was used to evaluate statistical significance between EAC and other fractures.Conclusion: Tympanic plate of EAC can fracture depending on the force against to it in MFT. In the assessment of maxillofacial trauma patients, CBCT images should be carefully evaluated not to overlook EAC fractures.KEYWORDS